METODE DAN STRATEGI PENGAJARAN PENDIDIKAN ISLAM TERHADAP GENERASI MILENIAL - Balya Ziaulhaq Achmadin; Abdul Fattah; Marno Marno (Journal of Research and Thought on Islamic Education (JRTIE), 2022)
Teaching methods in education are fundamental in achieving optimal learning outcomes. Active and effective learning methods can motivate students to develop their potential, starting from personality intelligence, morals or character, as well as social skills in society. The development of Islamic religious education in Indonesia is very famous. so that whenever and anyone who studies it will easily get various sources about Islamic education. Islamic education is very important in all times, especially the current era of globalization which is better known as the milenial era, the times of course have an influence on Islamic education in Indonesia, this raises new challenges in the world of education. In the current milenial era, there are so many technologies that facilitate the learning system, this is a challenge for us to utilize and manage technology for the sake of being wiser and useful for the development of Islamic education. because the teaching of Islamic education must develop according to the times without reducing Islamic traditions previous. The data collection process in this article uses a qualitative descriptive approach with literature methods and relative thinking which consists of finding, formulating, and identifying problems. The material obtained from the research results will be transcribed and analyzed. The results of this study obtained an effective and efficient method in delivering Islamic education materials, including using the conversational method (hiwar) of the Qur'an and Nabawi, the history of the Qur'an and Nabawi story, Amtsal Qur'ani and nabawi, exemplary, practice and habituation, ibrah or wisdom, targhib and tarhib that are adapted to the lives of the current milenial generation.